A visual dictionary of architecture - Ching, Frank, 1943- (Hoboken, N.J. : Wiley, 2012)
'Over 66 basic aspects of architecture are comprehensively covered with over 5,000 words in a visual context, to help visual thinkers clarify meanings. Comprehensive index permits the reader to locate any important word in the text. Oversized pages help present complicated material in easy-to-comprehend spreads. - Written by one of the most famous architectural authors --Frank Ching's name alone is a key selling feature for this book--he has earned the respect and trust of designers, design educators, and students around the world'--
Includes index.
Keywords: Architecture -- Dictionaries; Picture dictionaries, English